Integración de recursos virtuales LIVEWORKSHEETS y BAAMBOOZLE para la enseñanza y aprendizaje de Química con estudiantes de primero BGU del Colegio de Bachillerato Fiscal Chambo. - Chicaiza Duicela, Angélica Elizabeth (2023)
The purpose of this research was to integrate LIVEWORKSHEETS and BAAMBOOZLE virtual resources for the teaching and learning of Chemistry with first-year BGU students of the Chambo Fiscal Baccalaureate School. It has been possible to identify the learning of Chemistry, such as the chemical elements and the periodic table, is of great importance because it allows students to understand what surrounds us; In the same way, it could be mentioned that the application of technological tools such as educational platforms will improve student attention, thus promoting learning. Methodologically, a quantitative approach was used, with a non-experimental field and cross-sectional bibliographic design, the population was made up of first-year high school students from the Chambo Fiscal High School, their sampling was non-probabilistic in intencional, the techniques used used were the survey and the instrument the questionnaire, it was thus concluded that, through the socialization of the chemistry contents using the LIVEWORKSHEETS and BAAMBOOZLE applications with the first-year BGU students of the Chambo Fiscal Baccalaureate school, it allowed generating a feedback of these topics, which benefited the students' knowledge about the atomic model, atoms and the periodic table.